Developing a Validated Instrument to Measure Students’ Active Learning and Actual Use of Information and Communication Technologies for Learning in Saudi Arabia’s Higher Education - Almulla, Mohammed Abdullatif (Frontiers in Psychology, 2022)
Higher education authorities have supplied information and communication technologies (ICTs) to guarantee that students use ICT to improve their learning, and research outputs. ICT, on the other hand, has been proven to be underused, particularly by students. Therefore, aimed to developing a new model to measure students' active learning and actual use ICT in higher education. To investigate this issue, the technology acceptance model and constructivism learning theory were verified and applied to evaluate university students' use ICT for active learning purposes. The participants in the study were 317 postgraduate and undergraduate students from four faculties at King Faisal University who consented to take part. The research data was analyzed using structural equation modeling (AMOS-SEM).There were three specific components that were used: the technology adoption model, constructivism learning, and active learning using ICT. The findings revealed that: (a) using ICTs for students' interactivity, engagement, expected effort, subjective norm, and perceived ease of use has a direct positive impact on perceived enjoyment and usefulness; (b) perceived enjoyment and usefulness has a direct positive impact on active learning, attitude toward use, and behavioral intention to use ICTs; (c) active learning has a direct positive impact on attitude toward use, behavioral intention to use ICTs; and (d) active learning has a direct positive impact on attitude. Moreover, the results showed the mediator factors' values positively "R square", active learning (0.529), attitude toward use (0.572), behavioral intention to use (0.583), and actual ICT use (0.512) in higher education. Therefore, the results hypotheses, developed a validated instrument to measure students' active learning and actual use ICTs in higher education in Saudi Arabia's higher education.